2020
DOI: 10.1017/jfm.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Exhausting the background approach for bounding the heat transport in Rayleigh–Bénard convection

Abstract: We revisit the optimal heat transport problem for Rayleigh-Bénard convection in which a rigorous upper bound on the Nusselt number, N u, is sought as a function of the Rayleigh number Ra. Concentrating on the 2-dimensional problem with stress-free boundary conditions, we impose the full heat equation as a constraint for the bound using a novel 2-dimensional background approach thereby complementing the 'wall-to-wall' approach of Hassanzadeh et al. (J. Fluid Mech. 751, 627-662, 2014). Imposing the same symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…It is interesting that the power exponent of the bound on heat flux in penetrative convection is the same as that in the classical Rayleigh–Bénard convection (; Plasting & Kerswell 2003). However, as discussed in Ding & Kerswell (2020), the upper bound is not observable because there is no field satisfying the momentum and energy equations. This does not mean that the scaling (usually referred to as the ultimate scaling in classical Rayleigh–Bénard convection) is wrong at very large , but their analysis suggested that any true scaling should be lower than the bound.…”
Section: Optimal Heat Transfer By Steady Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that the power exponent of the bound on heat flux in penetrative convection is the same as that in the classical Rayleigh–Bénard convection (; Plasting & Kerswell 2003). However, as discussed in Ding & Kerswell (2020), the upper bound is not observable because there is no field satisfying the momentum and energy equations. This does not mean that the scaling (usually referred to as the ultimate scaling in classical Rayleigh–Bénard convection) is wrong at very large , but their analysis suggested that any true scaling should be lower than the bound.…”
Section: Optimal Heat Transfer By Steady Solutionsmentioning
confidence: 99%
“…It is noted that the upper bound on heat flux is at least an order higher than the numerical and experimental data at high Rayleigh numbers. Recent study by Ding & Kerswell (2020) demonstrated that the upper bound derived from the background method, however, is not observable, because there is no steady state satisfying the momentum equation.…”
Section: Introductionmentioning
confidence: 99%
“…Here the subscript marks the th critical mode of the energy stability problem. In general, the energy stability eigenvalue problem will have multiple critical eigenfunctions which need to be kept marginal – or ‘pinned’ (Ding & Kerswell 2020) – as the baffle is adjusted. Keeping track of new critical modes which emerge as is increased is a crucial part of solving this problem and considerable experience of handling this has been built up in the complementary problem of bounding the energy dissipation rate in turbulent flow (Plasting & Kerswell 2003, 2005; Ding & Kerswell 2020).…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…. The same argument can be applied to subsequent bifurcations (Ding & Kerswell 2020) assuming that is generically non-zero at each bifurcation. Since is always 1-D for as , we assume is 1-D for as well.…”
Section: Figure 11mentioning
confidence: 99%
“…Rayleigh-Bénard convection [10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] [ 20,21,30,31,[33][34][35][36][37][38], [39] † Bénard-Marangoni convection [40,41] [42] Porous-media convection [43] [ [44][45][46] Internally heated convection [26,[47][48][49][50][51] [50, 51] Double-diffusive convection [52] none Horizontal convection [53] none Parallel shear flows [7,8,11,15,…”
Section: Flow Analysis Computationsmentioning
confidence: 99%